Predictive value of valgus head-shaft angle in identifying Neer 4-part proximal humerus fractures. A radiographic and CT-scan analysis of 120 cases - Murena, Luigi; Ratti, Chiara; Maritan, Guido; Rasio, Nicholas; Grandesso, Maria; Barbati, Giulia; Cusitore, Marcello; Canton, Gianluca (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Understanding the fracture morphology and its relation to the expected outcome and risk of complications is fundamental for proximal humerus fractures (PHFs) management. Most Neer 3- and 4-part fractures may deserve surgical treatment. Unfortunately, plain x-rays may not be able to differentiate between a 3- or 4-part fractures unless an axillary or analogue projection is carried out. Aim of the present study is to evaluate whether a high valgus head-shaft angle degree is predictive of a Neer 4-part rather than a 3-part fracture. Methods: The study included 120 3-(75 cases) and 4-(45 cases) part PHFs (valgus displaced in 98 cases), M:F ratio = 1:2.6, mean age 65.7 years, classified on CT scan images. The humeral head shaft angle was calculated on AP x-rays and statistically correlated with 3 and 4-part fractures to identify values predictive of 4-part fracture. Results: Valgus head/shaft angle was significantly higher in 4-part fractures, especially in the valgus displaced group (p < 0.001). A cutoff value of 168.5° was identified as predictive of a 4-part fracture with a sensibility of 74% and specificity of 78%. Increasing by 1 degree the humeral head-shaft angle, the chance to have a 4-part fracture increases of 3% in the whole population and of 11% in the valgus sub-group. Conclusion: The severity of PHF can be predicted analysing valgus head shaft angle on AP x-rays with a sensibility of 74% and specificity of 78% in identifying a 4-part fracture with a cutoff value of 168.5°.